Comparing commercial pharmacogenetic testing results and recommendations for antidepressants with established CPIC guidelines - Nguyen, Tiffany T.; Leary, Emili J. W.; Lee, Joshua T.; Shukla, Sanjay K.; Griesbach, Sara A. (Frontiers in Pharmacology, 2024)
Introduction: Increasingly, pharmacogenetic testing helps providers with medication selection based upon patient-specific DNA results. While several government-funded organizations work towards consensus and standardization for testing and interpretation, compliance to these best practices remains inconsistent. Pharmacogenetic testing companies often develop proprietary practices for interpreting and reporting, which can lead to incongruency of reported results among companies and potential discrepancies in interpretation. Methods: To identify the differences of commercial pharmacogenetic testing vendors’ interpretation of genotype-to-phenotype translations and medication recommendations from the Clinical Pharmacogenetic Implementation Consortium (CPIC) guidelines, a retrospective manual chart review was completed in a large rural healthcare system that utilizes two institution-approved pharmacogenetic vendors. One hundred patients were evaluated: 50 who completed testing through Company A and 50 who completed testing through Company B. Genes of interest for genotype-to-phenotype translation included CYP2B6, CYP2C19, and CYP2D6. Comparison of medication recommendations for drug-gene pairs sertraline (CYP2B6 and/or CYP2C19), escitalopram (CYP2C19), and paroxetine (CYP2D6) were compared with recommendations from CPIC, with consideration of the CPIC Serotonin Reuptake Inhibitor Antidepressants (SSRI) guideline 2023 update. This was accomplished via a novel binning process to enable comparison of company-provided binned medication recommendations with CPIC guideline recommendations. Briefly, the binning system included three categorizations based upon the relevant CPIC guideline recommendations – no action needed (green), recommend monitoring (yellow) and therapeutic intervention or alternative recommended (red). Results: There were 32/250 (12.8%) genotype-to-phenotype translation discrepancies from CPIC guidelines, all from Company A. Of 266 evaluated binned medication recommendations, there were 114 (42.9%) discrepancies between the pharmacogenetic testing companies (Company A: 93 discrepancies, Company B: 21 discrepancies) and CPIC’s guideline based upon comparison with the novel binning system. Discussion: Significant differences were observed between testing companies’ interpretations and recommendations, which is concerning as these discrepancies could lead to providers making medication decisions that are not supported by CPIC’s clinical practice guidelines. This may result in suboptimal outcomes for patients, leading to patient and provider dissatisfaction and erosion of trust with pharmacogenetic testing. A proposed resolution for the discrepancies in company-to-company interpretation is adherence to the CPIC guidelines and transparency in interpretation practices.